RETRACTED: Elevated Expression Levels of PC3-Secreted Microprotein (PSMP) in Prostate Cancer Associated With Increased Xenograft Growth and Modification of Immune-Related Microenvironment - Pei, Xiaolei; Zheng, Danfeng; She, Shaoping; Fang, Zhiwei; Zhang, Shiying; Hu, Hao; Xu, Kexin; Wang, Ying (Frontiers in Oncology, 2019)
Prostate cancer (PCa), especially metastatic PCa, is one of the main cancer types accounting for male mortality worldwide. Over decades, researchers have tried to search for effective curative methods for PCa, but many attempts have failed. The therapeutic failure of PCa is usually due to off-target or side effects; thus, finding a key molecule that could prevent PCa metastatic progression has become the most important goal for curing aggressive PCa. In this study, we collected hundreds of PCa tissues and serum and urine samples from patients to verify the upregulated expression of PSMP in PCa tumor tissues with high Gleason scores. According to biopsies result, PSMP expression was found related to extraprostatic extension (EPE), contributing to PCa metastasis. Mechanistically, recombinant PSMP protein could promote the proliferation both in vitro and in vivo, and rhPSMP could promote epithelial-mesenchymal transition of PC3 in vitro. Additionally, PSMP could also influence the cytokines production in a xenograft model and monocyte migration and macrophage polarization in vitro. Our most important finding was that neutralizing antibodies against PSMP could suppress xenograft PC3 growth and promote the survival of PC3 metastatic mice model, might provide an effective option to cure human PCa.